Metric-rhyming system of the Adyghe verse: problems of formation and development - Lyudmila B. Khavzhokova (Кавказология)
The article examines the metric-rhyming system of the Adyghe (Kabardian, Circassian, Adygheyan) literary verse. Metrics and rhyme, as well as the versification system, haven’t become the subject of special study to this day, which is the reason this stated topic is addressed. The primary attention, on one hand, is focused on the specifics of the syllabic-tonic meters (trochee, iambic, dactyl, amphibrach, anapest) development and the features of their functioning in different genres and genre forms, but on the other hand, the evolution of rhyme in national poetry is traced. The scientific novelty of the work lies in the first attempts to make a comprehensive study of the metrical-rhyming system of the Adyghe verse at all stages of its development. Based on the results obtained, it is established that in the written poetry of the Circassians during the initial period of evolution, the “double rhyme” was applied; to date, all syllabi-tonic poetic meters in their multi-footed variations have been widely developed.